Identification Of Fresh Cardiorespiration Of 2018 Nusa Cendana University Of Penjaskesrek Students During Covid-19 - Yudabbirul Arif; Lukas M Boleng; Michael J. H. Louk; Ronald Dwi A Fufu (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
During the pandemic, online lectures are mandatory however, how can students' physical activity be maintained or not. The goal is that students who have good cardiorespiratory freshness are expected to have good endurance. This research is a qualitative descriptive study. The method used is a survey with data collection techniques using measurement tests. The instrument used to determine the endurance level of a student's physical fitness was a multi-stage running test or the bleep test. The sample in this study using simple random sampling, the research sample was selected as many as 30 students. The results of the data from 30 Penjaskesrek class 2018 Nusa Cendana University students who took the multistage fitness test to find out the level of cardiorespiratory freshness was in the very poor classification of 10 people with a percentage of 33.33%, the lack of classification was 3 people (10%), the classification is quite good (33.33%), good classification 5 people (16.66%), very good classification 2 people (6.66%), and no student is in the special classification (0%). The results show that the level of cardiorespiratory freshness The 2018 Nusa Cendana University Penjaskesrek students are in a sufficient classification.